Apples and pumpkins - Rockwell, Anne F.; Rockwell, Lizzy (New York : Macmillan ; London : Collier Macmillan, 1989)
In preparation for Halloween night, a family visits Mr. Comstock$1 (Bs farm to pick apples and pumpkins.s
Keywords: Autumn -- Fiction; Halloween -- Fiction; Apples -- Fiction; Pumpkin -- Fiction